2011
DOI: 10.1143/apex.4.065002
|View full text |Cite
|
Sign up to set email alerts
|

Patterned Growth of TiO2Nanowires on Titanium Substrates

Abstract: Single-crystalline rutile TiO2 nanowires (NWs) were synthesized by the vapor–liquid–solid (VLS) method on Ti foil substrates patterned with catalytic Sn nano-islands. NWs of 3 to 8 µm in length and 50 to 500 nm in diameter were grown along the [110] axis exhibiting a rectangular cross section with the (001) and (110) side facets. This facile approach to TiO2 NW fabrication with fast induction heating and short processing time utilizes the Ti foil both as a substrate and as a metal supply, thus eliminating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…Fabrication of semiconductor and oxide nanowires typically uses dewetting of a low melting point metal catalyst where the resulting clusters set the feature size while epitaxy to the underlying substrate can control the growth orientation. 5,[35][36][37] More recently, an electrochemical electrolyte-liquid-solid analog has been demonstrated for growth of Ge nanowires. [38][39][40] In another approach nanowire growth of metallic nanostructures capitalizes on the intrinsic or additive engineered anisotropic energetics and/or growth kinetics on different crystal facets.…”
mentioning
confidence: 99%
“…Fabrication of semiconductor and oxide nanowires typically uses dewetting of a low melting point metal catalyst where the resulting clusters set the feature size while epitaxy to the underlying substrate can control the growth orientation. 5,[35][36][37] More recently, an electrochemical electrolyte-liquid-solid analog has been demonstrated for growth of Ge nanowires. [38][39][40] In another approach nanowire growth of metallic nanostructures capitalizes on the intrinsic or additive engineered anisotropic energetics and/or growth kinetics on different crystal facets.…”
mentioning
confidence: 99%
“…It is due to the thickness of Ti layer we deposited. According to the result of Ha et al, they got 3∼8 μm long TiO2 nanowires on Ti layer [17]. They used Ti foil and deposited Ti thin film as sufficient source of nanowire growth.…”
Section: Resultsmentioning
confidence: 99%
“…There are previous studies of nanowire growth using Vapor-Liquid-Solid (VLS) process with metal catalyst [13][14][15][16][17][18][19][20]. Generally, it is reported that TiO2 nanowire grows at 800∼900 o C using VLS process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, ZnO nanowires have been grown from an anodic alumina membrane (AAM) by combining with a vapour deposition process [103,104].…”
Section: Vapour Deposition Growth Of 1d Nanostructuresmentioning
confidence: 99%